Isolasi Candida albicans Dari Swab Mukosa Mulut Penderita Diabetes Melitus Tipe 2 - Kadek Sri Jayanti, Ni; Jirna, I Nyoman (POLTEKKES KEMENKES YOGYAKARTA, 2018)
Candida albicans can be pathogen when immunity had decreased and physiological function is impaired, such as in diabetes mellitus type 2. This study aims to isolation Candida albicans that collected from the oral cavity of diabetes mellitus type 2 patients. This research is conducted with a descriptive study by observing the presence of Candida albicans in 30 samples of diabetes mellitus type 2 patients, which grows on Potato Dextrose Agar. The microscopic observation by LPCB staining of yeasts, blastospores, pseudohyphae, chlamydospores and germ tubes in human serum suspension that incubated at 370C for 2-3 hours. Based on this research was found 14 (46,7%) patients from 30 patients were positive Candida albicans.